Synthesis and thermoelectric properties of Ca3Co4O9 prepared by sol-gel method using ova - Lerssongkram, Neungnuch; Pinitsoontorn, Supree; Keawprak, Nittaya (Asia-Pacific Journal of Science and Technology, 2017)
Thermoelectric Ca3Co4O9 powder was synthesized by a sol-gel method using an aqueous solution containing metal nitrates and polyvinyl alcohol (PVA) as starting materials. The physical properties of the samples were characterized by thermogravimetric/ differential thermal analysis (TG/DTA), x-ray diffraction (XRD), energy dispersive x-ray analysis (EDX) and scanning electron microscopy (SEM). The single phase of Ca3Co4O9 compound was obtained at the calcined temperature of 800 °C for 4 h. The polycrystalline bulk samples were compacted by a uniaxial pressure of 440 MPa and then sintered at 890 °C for 4 h. The thermoelectric properties of the sintered samples were investigated from room temperature to 600 °C. At 600°C the electrical resistivity, the Seebeck